Observation of superior and inferior limit of lobes of the thyroid gland: a postmortem study - Banna, MH; Sultana, Z; Khalil, M; Begum, JA (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):431-435 The abstract of this article is available on the PubMed website